Role of Internal Jugular Vein Ultrasound Measurements in the Assessment of Central Venous Pressure in Spontaneously Breathing Patients: A Systematic Review - Parenti, Nicola (J Acute Med, 2019)
BACKGROUND: Few studies have tested the role of the internal jugular vein (IJV) ultrasonographic (US) diameters in the assessment of central venous pressure (CVP) in spontaneously breathing patients. No review or meta-analysis is currently available on the role of IJV assessment in this setting. The aim of this systematic review is to check the reliability and accuracy of IJV US diameters in predicting CVP and to evaluate its correlation with CVP in spontaneously breathing patients. METHODS: This systematic review was based on the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. We included studies on the accuracy and reliability of the IJV ultrasound measures and studies exploring its correlation with CVP in adult spontaneously breathing patients. The studies’ report quality was assessed by Standards for Reporting of Diagnostic Accuracy (STARD) and Quality Assessment of Diagnostic Accuracy Studies (QUADAS)-2 scales. RESULTS: A total of five studies was eligible for final analysis. The studies on IJV ultrasound measures showed a good quality in reporting. The anterior-posterior diameter maximum of IJV (AP-IJV Dmax) showed the best correlation with the CVP with a good inter-rater reliability and validity in predicting CVP. All measures showed good inter-rater reliability and validity in predicting CVP, but only the AP-IJV Dmax showed good correlation with CVP. CONCLUSIONS: The AP-IJV Dmax could be a potential surrogate of CVP because of its good reliability and validity in predicting CVP value and its fair-moderate correlation with CVP. Anyway, further research should confi rm these conclusions.